The relationship between ppe use and work accidents among firefighters in Pinrang 2025 - Rudini, Muh.; Marwah , Marwah; Taslim , Taslim; Armadi , Armadi; Sudirman , Sudirman; Sudirman (Institute Of Computer Science (IOCS), 2025)
Firefighting is a high-risk occupation that requires strict implementation of occupational safety measures, including the consistent use of personal protective equipment (PPE). Despite existing safety regulations, work accidents among firefighters remain a global concern. This study aimed to analyze the relationship between PPE use and the incidence of work accidents among firefighters at the Watang Sawitto Subdistrict Fire Station in Pinrang Regency. Using a quantitative cross-sectional design with total sampling, all 52 firefighters were included as respondents. Data were analyzed using the Chi-square test to examine the correlation between PPE use and work accidents. The results showed a significant relationship (p = 0.001), indicating that incomplete PPE use increases the likelihood of occupational accidents. This finding highlights the importance of strengthening compliance with PPE standards and institutional safety management systems to reduce occupational risks among firefighters. The study contributes scientifically by providing empirical evidence on the role of PPE adherence in preventing workplace accidents in high-risk emergency service environments, and practically by offering insights for policy development and safety interventions within Indonesia’s occupational health and safety (K3) framework.